Fotocatalisadores à base de nitreto de carbono grafítico (g-C3N4) com aplicação em fotocatálise heterogênea sob irradiação de luz solar visando a degradação de diclofenaco de sódio - Batista, José André Ferreira (2024)
Four photocatalysts (g-C3N4, g-C3N4/Cl, g-C3N4/Nb2O5, and g-C3N4/TiO2) were synthesized successfully using straightforward methods. All photocatalysts exhibited visible-light absorption extending beyond 400 nm, indicative of their responsiveness to visible light. No statistically significant differences in diclofenac degradation performance were observed among the studied photocatalysts within the investigated time intervals (240 min). However, the specific constant rate normalized by SBET revealed that bare g-C3N4 exhibited a 4.9-fold higher Kinect constant compared to the average of the other three photocatalysts combined. This finding suggests that unmodified g-C3N4 photocatalyst is adequate for promoting diclofenac degradation, without the need for heterojunction fabrication or chloro-doping. The degradation efficiency of diclofenac under natural sunlight irradiation using unmodified g-C3N4 showed that the normalized illumination time (t30w) required for degradation over 67% was 68 minutes, achieving accumulated UV and VIS energy values of 13.44 and 1259 KJ.m-2 , respectively. Notwithstanding the diminished efficacy in comparison to results achieved under artificial sunlight, the photocatalysis under natural sunlight underscores the photocatalyst's capacity to exploit g-C3N4 for the degradation of the diclofenac. Concerning phytotoxicity assessment, a total of 14 assays were performed utilizing the four photocatalysts and two seed varieties (cucumber and lettuce). With some exceptions (notably g-C3N4, g-C3N4/Cl, and g-C3N4/TiO2, but solely for cucumber seeds), all trials indicated that the byproducts resulting from diclofenac photocatalysis, whether under artificial or natural sunlight, were non phytotoxic. This was evidenced by germination indices surpassing 80%, suggesting the potential utilization of these byproducts for water recycling in irrigation purposes.